Tax Policy Implications in Endogenous Growth Models - Xu, Bin. (Washington, D.C. : International Monetary Fund, 1994)
This paper surveys the tax policy implications in various endogenous growth models. The focus is on the long-run growth effects of income, consumption, and investment taxation in models whose engine of growth is the accumulation of human capital, technological innovation, and/or public infrastructure. The results depend on model specifications. This paper also reviews quantitative results from cross-country regressions and simulations, and indicates some statistical and methodological problems to which they are subject. Tax policy implications in endogenous growth models both with tax policy endogenously determined by a political process and with international capital mobility are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet